The marine food web of the Malpelo Fauna and Flora Sanctuary, Colombia: a structural analysis from a topological approach - Colombo Estupiñán-Montaño; Alberto Sánchez-González; Felipe Galván-Magaña; Fernando R. Elorriaga-Verplancken; Manuel J. Zetina-Rejón; Carlos J. Polo-Silva (Theoretical Ecology, 2026)

MIL-53(Fe)-mediated persulfate activation for the removal of pesticides-contaminated water: phytotoxicity evaluation, theoretical reactivity prediction and by-products degradation pathways - Muriel R. Affonso; Igor G.S. Oliveira; Fernando C. Gallina; Beatriz T. Marin; João P.P. Encide; Micael M. Baruch; Robson S. Souto; Renata Colombo; Kathia M. Honorio; Marcos R.V. Lanza; Willyam R.P. Barros (Chemical Engineering Journal, 2026)

Corrigendum to “Hydrothermal geochemical signatures in zircon as a pathfinder for IOCG mineralization: An example from the Carajás Mineral Province (Brazil)” [J. Geochem. Explor. 281,107934 (2026)] - Maurício L. Borba; Colombo C. Tassinari; Fernando M. Matos; John M. Hanchar; Fernando Tornos; Sergio Huhn; Kei Sato (Journal of Geochemical Exploration, 2026)

Hydrothermal geochemical signatures in zircon as a pathfinder for IOCG mineralization: An example from the Carajás Mineral Province (Brazil) - Maurício L. Borba; Colombo C. Tassinari; Fernando M. Matos; John M. Hanchar; Fernando Tornos; Sergio Huhn; Kei Sato (Journal of Geochemical Exploration, 2026)

Correction to: Ontogenetic feeding ecology of the silky shark (Carcharhinus falciformis) in the Colombian eastern tropical Pacific - Colombo Estupiñán‑Montaño; Daniel J. Villalobos‑Ramírez; Felipe Galván‑Magaña; Fernando R. Elorriaga‑Verplancken; Manuel J. Zetina-Rejón; Alberto Sánchez‑González; Carlos J. Polo‑Silva; Antonio Delgado‑Huertas (Environmental Biology of Fishes, 2025)

Ontogenetic feeding ecology of the silky shark (Carcharhinus falciformis) in the Colombian eastern tropical Pacific - Colombo Estupiñán-Montaño; Daniel J. Villalobos-Ramírez; Felipe Galván-Magaña; Fernando R. Elorriaga-Verplancken; Manuel J. Zetina-Rejón; Alberto Sánchez-González; Carlos J. Polo-Silva; Antonio Delgado-Huertas (Environmental Biology of Fishes, 2025)

Marine community trophic structure of Malpelo Island, Colombia from stable isotopes approach - Colombo Estupiñán-Montaño; Carlos J. Polo-Silva; Fernando R. Elorriaga-Verplancken; Alberto Sánchez-González; Manuel J. Zetina-Rejón; Antonio Delgado-Huertas; Jaiver Rojas-Cundumí; Felipe Galván-Magaña (Journal of Marine Systems, 2024)

Characterization of ESBL/AmpC-producing extraintestinal Escherichia coli (ExPEC) in dogs treated at a veterinary hospital in Brazil - Brendhal Almeida Silva; Victor Santos do Amarante; Rafael Gariglio Clark Xavier; Salene Angelini Colombo; Tales Fernando da Silva; Bertram Brenig; Flavia Figueira Aburjaile; Vasco Ariston de Carvalho Azevedo; Rodrigo Otávio Silveira Silva (Research in Veterinary Science, 2024)

The impact of Li-bearing pegmatite mining on the dissolved geochemical signature of a mountain stream in the Pampean ranges, Central Argentina - Milagros Marqués; Andrea I. Pasquini; María Gabriela García; Verena A. Campodonico; Fernando Colombo; Diego M. Gaiero; Karina L. Lecomte (Sustainable Water Resources Management, 2023)

Trophic connectivity between the terrestrial and marine ecosystems of Malpelo Island, Colombia, evaluated through stable isotope analysis - Colombo Estupiñán-Montaño; Manuel J. Zetina-Rejón; Felipe Galván-Magaña; Antonio Delgado-Huertas; Fernando R. Elorriaga-Verplancken; Carlos J. Polo-Silva; Javier Rojas-Cundumí; Daniel J. Villalobos-Ramírez; Alberto Sánchez-González (Marine Biology, 2023)

Evaluation of Infiltration Models with Different Numbers of Adjustment Parameters in an Oxisol with Application of Wastewater at the Different Concentrations - Júlia Fonseca Colombo Andrade; Luiz Fernando Coutinho de Oliveira; Jaíza Ribeiro Mota e Silva (Water, Air, & Soil Pollution, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Tracking rock sources of 3800-year-old burial goods using X-ray diffraction, electron microprobe analyses and X-ray mapping: a case study from Córdoba, Argentina - Fernando Colombo; Gisela Sario; Sandra Gordillo; Mariana Fabra (Rendiconti Lincei. Scienze Fisiche e Naturali, 2020)

New insights into the trophic ecology of young white sharks (Carcharodon carcharias) in waters off the Baja California Peninsula, Mexico - Elena Tamburin; Fernando R. Elorriaga-Verplancken; Colombo Estupiñan-Montaño; Daniel J. Madigan; Alberto Sánchez-González; Mauricio Hoyos Padilla; Michelle Wcisel; Felipe Galván-Magaña (Marine Biology, 2020)

Dietary ontogeny of the blue shark, Prionace glauca, based on the analysis of δ13C and δ15N in vertebrae - Colombo Estupiñán-Montaño; Felipe Galván-Magaña; Alberto Sánchez-González; Fernando R. Elorriaga-Verplancken; Antonio Delgado-Huertas; Diego Páez-Rosas (Marine Biology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Early Invasive Pulmonary Aspergillosis in a Kidney Transplant Recipient Caused by Aspergillus lentulus: First Brazilian Report - Viviane Reis de Azevedo Bastos; Daniel Wagner de Castro Lima Santos; Ana Carolina Barbosa Padovan; Analy Salles Azevedo Melo; Milene de Abreu Mazzolin; Luis Fernando Aranha Camargo; Arnaldo Lopes Colombo (Mycopathologia, 2015)

Induction of ferritin synthesis by water deficit and iron excess in common bean (Phaseolus vulgaris L.) - Daiane Mariele DeLaat; Carlos Augusto Colombo; Alisson Fernando Chiorato; Sergio Augusto Morais Carbonell (Molecular Biology Reports, 2014)

In Vitro Susceptibility of a Large Collection of Candida Strains Against Fluconazole and Voriconazole by Using the CLSI Disk Diffusion Assay - Ana Carolina Azevedo; Fernando César Bizerra; Daniel Arquimedes da Matta; Leila Paula de Almeida; Robert Rosas; Arnaldo Lopes Colombo (Mycopathologia, 2011)

Structure of genetic diversity among common bean (Phaseolus vulgaris L.) varieties of mesoamerican and andean origins using new developed microsatellite markers - Luciana Lasry Benchimol; Tatiana de Campos; Sérgio Augusto Morais Carbonell; Carlos Augusto Colombo; Alisson Fernando Chioratto; Eduardo Fernandes Formighieri; Lígia Regina Lima Gouvêa; Anete Pereira de Souza (Genetic Resources and Crop Evolution, 2007)

Structure of genetic diversity among common bean (Phaseolus vulgaris L.) varieties of Mesoamerican and Andean origins using new developed microsatellite markers - Luciana Lasry Benchimol; Tatiana de Campos; Sérgio Augusto Morais Carbonell; Carlos Augusto Colombo; Alisson Fernando Chioratto; Eduardo Fernandes Formighieri; Lígia Regina Lima Gouvêa; Anete Pereira de Souza (Genetic Resources and Crop Evolution, 2007)

Multiple sources for ore-forming fluids in the Neves Corvo VHMS Deposit of the Iberian Pyrite Belt (Portugal): strontium, neodymium and lead isotope evidence - Jorge M. Relvas; Colombo C. Tassinari; José Munhá; Fernando J. Barriga (Mineralium Deposita, 2001)